A CLASS OF NON-STANDARD SPECTRAL PROBLEMS - Gegovska-Zajkova, Sonja (Matematichki Bilten, 2002)
We consider parabolic equations in two dimensions with interface corresponding to concentrated heat capacity and singular own source. We study non-standard spectral problems in which the eigenvalue appears in the conjugation conditions or at the boundary of the spatial domain.